If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + -16a) = -2a + -6(a + -7) (1 * 2 + -16a * 2) = -2a + -6(a + -7) (2 + -32a) = -2a + -6(a + -7) Reorder the terms: 2 + -32a = -2a + -6(-7 + a) 2 + -32a = -2a + (-7 * -6 + a * -6) 2 + -32a = -2a + (42 + -6a) Reorder the terms: 2 + -32a = 42 + -2a + -6a Combine like terms: -2a + -6a = -8a 2 + -32a = 42 + -8a Solving 2 + -32a = 42 + -8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8a' to each side of the equation. 2 + -32a + 8a = 42 + -8a + 8a Combine like terms: -32a + 8a = -24a 2 + -24a = 42 + -8a + 8a Combine like terms: -8a + 8a = 0 2 + -24a = 42 + 0 2 + -24a = 42 Add '-2' to each side of the equation. 2 + -2 + -24a = 42 + -2 Combine like terms: 2 + -2 = 0 0 + -24a = 42 + -2 -24a = 42 + -2 Combine like terms: 42 + -2 = 40 -24a = 40 Divide each side by '-24'. a = -1.666666667 Simplifying a = -1.666666667
| 6x+11=8x+13 | | 3k-7k=-9-k | | 27=2y-13 | | -(-9-6x-6y)= | | 980+n=1020 | | E=(8) | | -5=3x+8 | | -4x+8=-12+x-8-7 | | -(4x-10)+2(3x+15)= | | 4x^3+24x^2+12x-40=0 | | 6x-3y+14w-5y-4w+9x= | | 592=2L+2(5L+6) | | 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= | | 19-u=238 | | -8(b-5)=-2(b+1) | | a-3[b-2(c-x)]=4 | | 167=2(3w-5)+2w | | 3x+6=9(x+4) | | 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) |